Pedra bonita as pedras que contam : aspectos socioeconômicos do ciclo da mineração de cassiterita no Vale do Jamari/sub-bacia do Rio Jacundá do fim da década de 50 à 90 - Santos, Anderson de Jesus dos (2014)
This work is the result of at least ten years of research since the development of the project, to the first interview and first cataloged documents in Historical Documentation Center of the Court of Rondônia. It discusses the social and economic relations in the current City of Itapuã do Oeste and the Jamari National Forest area, in the period that includes the mid 50s until the late 90s of XX century. During this period cassiterite comes to occupy a prominent place in the local economy since the rubber loses its economic importance in the region and its value in the international market. The end of manual mining in 1971 attracted for the region national companies and multinational groups, which changed some aspects of mineral exploration and working relationships in order to make them more human than they were in the days of the rubber and later of the mines. With the emergence of Itapuã do Oeste in the late 70 the differences between Itapuã do Oeste and the Jacundá Mining are immense in terms of the basic structures of care for the population, such as sanitation, prevention of endemic diseases, public lighting, education, etc. But with the breakdown of cassiterite in 1989/1990 in the international market, the cassiterite mining underwent a process of adaptation to the new reality imposed by the market, so a significant part of the population of Jacundá Mining that has not been fired began to settle in the Itapuã do Oeste at a time when the district Itapuã do Oeste is elevated to municipality.